Understanding Accounting Phenomena through Actor–Network Theory: A Review of Studies Published Between 2023 and 2025: English - Rissa Nadiah Afifah Sembiring; Sambas Ade Kesuma; Iskandar Muda; Firman Syarif (Pusat Riset dan Inovasi Nasional, 2026)
This study reviews the application of Actor–Network Theory (ANT) in accounting research published between 2023 and 2025, with the aim of enhancing understanding of accounting phenomena as socio technical practices. A systematic literature review (SLR) was conducted using the PICO (Population, Intervention, Comparison, Outcome) framework to define inclusion criteria and support thematic analysis. The final dataset consists of 33 peer-reviewed articles that were systematically collected and analyzed. The findings indicate a clear predominance of qualitative research methods, including case studies, ethnography, and discourse analysis. The reviewed studies emphasize the relational dynamics between human and non-human actors in accounting processes, illustrating how non-human elements such as information systems, technologies, and organizational infrastructures actively shape accounting practices, organizational tensions, and decision-making outcomes. This review contributes to the accounting literature by synthesizing recent ANT based studies and highlighting opportunities for future research, particularly through the integration of ANT with institutional theory and the use of mixed-method approaches to capture the complexity of contemporary accounting networks.